Legal Study of the Validity of Electronic Signatures (Digital Signatures) in Business Contracts - Selvia Wisuda (Universitas PGRI Madiun, 2023)
Problems in the civil sector because electronic transactions for business through electronic systems (e-commerce) have become part of domestic and international business. This shows that the correlation between the fields of informatics, media and informatics (telematics) continues to develop. Formulation of the status and legal strength of electronic signatures in commercial contracts and the validity of electronic signatures as evidence in the Indonesian Civil Procedure Law. Using this type of library research to collect scientific knowledge and information in the form of theories, methods or approaches that are developed and documented in the form of books, journals, manuscripts, notes, historical documents and other documents. An electronic contract is only valid if it can be ensured that all components of the electronic system can be trusted and/or function as they should